The Silence Behind Achievement: A Phenomenological Study on the Mental Health of Outstanding Students - Riska Adinda Putri Siregar; Anisah Fitri Tanjung; Syahnira Wan Aisyah Nasution; Uci Wardiana Harahap; Sarita Riski; Sandi Pradana (Madiha Press, 2025)
High-achieving students are often seen as strong and successful figures, but in reality, many of them experience hidden psychological stress. This study is important to reveal the silent side behind academic achievement that is often overlooked, especially related to mental health. This study aims to understand the subjective experiences of high-achieving students in dealing with academic and social pressure and how they respond to mental health conditions that arise as a result. The method used in this study uses a qualitative approach with a phenomenological study design. Data were collected through in-depth interviews with 15 active students at the State Islamic University who had a GPA ≥ 3.5 and had achieved academic or non-academic achievements. Data analysis was carried out using a thematic approach based on the Braun and Clarke procedure. The results of the study showed five main themes: achievement pressure and academic anxiety, social loneliness and alienation, coping strategies for stress, the need for social support, and the role of perfectionism in influencing mental conditions. High-achieving students were shown to experience high stress but had varying coping mechanisms. This study aims to emphasize the importance of the role of educational institutions in providing a safe and inclusive psychological support space for high-achieving students so that achievement can go hand in hand with mental well-being.